Integrating Halal Certification in Free Trade Agreements: Indonesia’s Modest Fashion and Cosmetics - Arina Nihayati (Jurnal Hubungan Internasional, 2025)
The global halal industry has become a crucial sector in international trade, with modest fashion and halal cosmetics emerging as key drivers of economic growth. Indonesia, as the country with the largest Muslim population, has positioned itself as a major player in the halal industry, supported by a robust regulatory framework and international trade agreements. This study examines the integration of halal certification in Free Trade Agreements (FTAs) and its impact on Indonesia’s halal product exports, particularly modest fashion and cosmetics, to the Middle East. Using a qualitative approach with document analysis, this research explores the challenges and opportunities faced by Indonesian exporters, focusing on regulatory harmonization, market access, and international competitiveness. Findings indicate that Indonesia’s halal certification system, governed by BPJPH and supported by Law No. 33 of 2014, aligns with international halal standards but faces difficulties in mutual recognition with Gulf Cooperation Council (GCC) countries. Despite the Indonesia-UAE Comprehensive Economic Partnership Agreement (CEPA) reducing trade barriers, non-tariff barriers such as certification redundancy and supply chain inefficiencies continue to hinder exports. The study reveals that Indonesia’s modest fashion and halal cosmetics sectors are experiencing rapid growth, with total halal exports reaching IDR 673.9 trillion in 2024. However, competition from Malaysia, Turkey, and the UAE, alongside challenges in e-commerce adoption, logistics, and branding, limit Indonesia’s global market share. To enhance international competitiveness, regulatory harmonization, supply chain improvements, digital transformation, and strategic branding initiatives are necessary. This research provides critical insights for policymakers, industry stakeholders, and scholars in Islamic economics and global trade, emphasizing the need for stronger diplomatic efforts, trade policy alignment, and digital capacity building to strengthen Indonesia’s position as a global halal industry leader. Keywords: Halal Certification; Free Trade Agreements; Modest Fashion; Halal Cosmetics; Indonesia